Relation between casein in nipple discharges of women with galactorrhea and hyperprolactinemia - (:unkn) unknown (My University, 2004)
Galactorrhea; the most common nipple discharge is the inappropriate secretion of milk which may occur spontenously or upon expression of the nipple in the absence of pregnancy or lactation. Nipple discharges may vary in color and consistency from clear or milky to bloody and, it can be benign process or an indicator of malignancy. However etiology of any nipple discharge should be investigated. Hyperprolactinemia is usually associated with galactorrhea, but about 28 to 55% of women may have normal prolactin levels and still experience galactorrhea. The differential diagnosis of galactorrhea syndromes is more complicated. The discharge is milk or not must be clarified. Since Prolactin (PRL) is the key lactogenic hormone in initiating milk protein; casein's m-RNA stimulation, determination of casein by radial-immunodiffusion (RID) can be indicative for hyperprolactinemia and in the differentiation of true galactorrhea in suspicious events. © 2004 Taylor and Francis Group, LLC.